Toxicity of Neem Cake Extract (Azadirachta indica) to Aphis glycine on Soybean Plant - Ratmaneli Ratmaneli; Danar Dono; Vira Kusuma Dewi (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2019)
Aphis glycine is one of the soybean pests that can develop rapidly and cause yield loss. Neem is a plant known as botanical incesticide. This study tested the toxicity of neem cake against A. glycine and its effect on increasing tannin content in the soybean plant. The effect of neem cake extract to the mortality of A. glycine was tested by spray method and root dipping method. The application was carried out on four-week-old soybean plants with 10 individual of adult A. glycine as test insects. Observations were carried out every day for 8 DAT (day after treatmen) by counting the population of A. glycine. The testing of tannin levels and azadirachtin content is done by applying neem cake extract using root dipping method. The treatment is divided into two groups, which are infested plants and non-invested plants by A. glycine. The leaf of soybean (fourth day after application) was taken as samples for tannin and azadirachtin analysis. The results showed that the extract of neem cake at the spray method caused the death of A. glycine up to 97% at a concentration 2.5%. The root dipping method could make mortality of nymphs (new born) 100% at concentrations of 0.1% and 0.125% at 8 DAT , but cannot make mortality to adult of A. glycine. The tannin content in soybean plants (with A. glycine and without A. glycine invested) was increased after 0.125% neem cake application. Azdirachtin uptake was not detected at concentrations of 0.125% and 0.250% at 5 DAT. Neem cake extract can suppress A. glycine population in soybean plants and increase of tannin content in plants.